Functioning and needs of patients with chronic mental illness attending a community mental health clinic in South India. - Kurian , Jose (International Journal of Psychosocial Rehabilitation, 2017)
Backgrounds & Objectives: One of the major challenges in the mental health care is the recovery from the mental illness. Understanding functioning and needs of the persons with mental illness is one of the tools through which the rehabilitation plans can be made effective. Methods: Outpatients ( 54) attending the Community Mental Health Programme (CMHP), at Thal kulathoor, a village in Kozhikode district of Kerala, India, was selected as study group. Pre-printed survey-based questionnaire were administered to the patients who attended the community clinic. The study is a single contact, cross-sectional study. Results: In the domains of   role functioning 77.8% of them were unable to make decisions regarding themselves or regarding the family matters and supervising family. 72.2%    of the sample was unable to earn money and handle them. Majority   of the selected sample (81.5 %) lacked problem solving skills and 70.4% had problems in maintaining interpersonal relations. Interpretations and conclusion:  The research looks into the deficiencies in the life of mentally ill in the community and  adopting remedial measures through rehabilitation.